Repair kinetics of acrolein– and (E)-4-hydroxy-2-nonenal–derived DNA adducts in human colon cell extracts - Choudhury, Sujata (2013)
ω-3 and ω-6 Polyunsaturated fatty acids (PUFAs) play a role in the pathogenesis of colon cancer. Upon oxidation, PUFAs generate α,β-unsaturated aldehydes or enals, such as acrolein (Acr) and (E)-4-hydroxy-2-nonenal (HNE), which can form cyclic adducts of deoxyguanosine (Acr-dG and HNE-dG, respectively) in DNA. Both Acr-dG and HNE-dG adducts have been detected in human and animal tissues and are potentially mutagenic and carcinogenic. In vivo levels of Acr-dG in DNA are at least two orders of magnitude higher than those of HNE-dG. In addition to the facile reaction with Acr, the higher levels of Acr-dG than HNE-dG in vivo may be due to a lower rate of repair. Previous studies have shown that HNE-dG adducts are repaired by the NER pathway (Choudhury et al., Biochemistry 43 (2004) 7514–7521). We hypothesize that Acr-dG adducts are repaired at a slower rate than HNE-dG and that HNE-dG in DNA may influence the repair of Acr-dG. In this study, using a DNA repair synthesis assay and a LC-MS/MS method, we showed that Acr-dG in a plasmid DNA is repaired by NER proteins, but it is repaired at a much slower rate than HNE-dG in human colon cell extracts, and the slow repair of Acr-dG is likely due to poor recognition/excision of the lesions in DNA. Furthermore, using a plasmid DNA containing both adducts we found the repair of Acr-dG is significantly inhibited by HNE-dG, however, the repair of HNE-dG is not much affected by Acr-dG. This study demonstrates that the NER repair efficiencies of the two major structurally-related in vivo cyclic DNA adducts from lipid oxidation vary greatly. More importantly, the repair of Acr-dG can be significantly retarded by the presence of HNE-dG in DNA. Therefore, this study provides a mechanistic explanation for the higher levels of Acr-dG than HNE-dG observed in tissue DNA.